Lemon grass oil for improvement of oral health - Ruckmani Rajesvari; T Lakshmi (Wolters Kluwer Medknow Publications, 2013)
Lemon grass essential oil has been used for decades to treat respiratory infections, sinusitis, bladder infections, high cholesterol, digestive problem, varicose veins and also for regeneration of connective tissue. It has anti spasmodic, anti-pyretic, anti-fungal, anti-bacterial, anti-inflammatory, anti-septic, insect repellent, sedative, vasodilator and flavoring properties. In china, it has been used traditionally as a remedy for stomach and liver diseases and also to treat rheumatism. Since lemon grass oil possess various pharmacological actions, it is also quite useful in dentistry. Hence, the objective of this article is to highlight various uses of lemon grass oil in the dental field and in the medical field in order to aid the professionals for future research.